2010
DOI: 10.1071/fp10010
|View full text |Cite
|
Sign up to set email alerts
|

Viewing leaf structure and evolution from a hydraulic perspective

Abstract: Abstract. More than 40 000 km 3 year -1 of water flows through the intricate hydraulic pathways inside leaves. This water not only sustains terrestrial productivity, but also constitutes nearly 70% of terrestrial evapotranspiration, thereby influencing both global and local climate (Chapin et al. 2002). Thus, the central role played by leaf vascular systems in terrestrial biology provides an important context for research into the function and evolution of water transport in leaves. Significant progress has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
233
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(243 citation statements)
references
References 99 publications
(121 reference statements)
9
233
0
1
Order By: Relevance
“…The developmental algorithm and scaling relationships we have shown makes this possible for dicotyledons, providing a strong ecological advantage. Dicotyledons can produce large leaves with both large major veins for mechanical support and high vein densities that enable transpirational cooling and high photosynthetic rates 1,[47][48][49] . Large simple leaves with high vein density are an angiosperm innovation, because the ongoing production of minor veins in expanding leaves depends on the plate meristem that is typically found only in angiosperms 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developmental algorithm and scaling relationships we have shown makes this possible for dicotyledons, providing a strong ecological advantage. Dicotyledons can produce large leaves with both large major veins for mechanical support and high vein densities that enable transpirational cooling and high photosynthetic rates 1,[47][48][49] . Large simple leaves with high vein density are an angiosperm innovation, because the ongoing production of minor veins in expanding leaves depends on the plate meristem that is typically found only in angiosperms 18 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a large leaf may be selected for a plant of a moist area, for effective light capture and photosynthesis relative to biomass allocation 44 , and a small leaf may be selected in drought-tolerant species 8 ; both may have high minor vein densities, enabling high photosynthetic rates when water is available. The potential of angiosperms to vary strongly in vein density enables dominance in a far greater range of habitats than other plant lineages 3,6,48 , especially as leaf size can adapt independently to optimise other ecological benefits against costs 6,7,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Since transpiration is directly linked to availability of water to roots, we hypothesised that LVD will 5 be correlated with depth-to-groundwater (DTGW) in plants for which groundwater is accessible; this correlation should be absent in species with shallow roots which cannot access groundwater. Whilst a number of studies have demonstrated increased LVD with increasing aridity along rainfall gradients (Brodribb et al, 2010;Brodribb and Holbrook, 2003;Sack and Holbrook, 2006), this relationship has not, to our knowledge, been examined in relation to DTGW. Finally, because LVD is strongly correlated with K leaf and rates of leaf-scale gas exchange Sack et al, 2003;Sack and 10 Frole, 2006), we hypothesise that LVD will be significantly correlated with Δ 13 C (and hence WUE i ).…”
mentioning
confidence: 89%
“…In order to gain carbon most economically while minimising water loss (i.e., optimization of the ratio A/E), stomata should function such that the marginal water cost of carbon assimilation ( ) remains constant (Cowan and Farquhar, 1977;Farquhar and Sharkey, 1982). This aspect of stomatal 20 control couples the structural traits involved with water-flow with traits associated with primary production (Brodribb and Holbrook, 2007) and explains observed correlations between K leaf and A max in a number of studies Brodribb et al, 2010;Brodribb et al, 2005;Brodribb and Jordan, 2008;Sack and Holbrook, 2006;Sack and Scoffoni, 2013). The length of hydraulic pathway is directly proportional to K leaf and the A/g s ratio determines foliar Δ 13 C (and WUE i ) signatures in leaves.…”
Section: Leaf Vein Density Across the Depth-to-groundwater Gradientmentioning
confidence: 99%
See 1 more Smart Citation